2014
DOI: 10.1111/jvim.12385
|View full text |Cite
|
Sign up to set email alerts
|

Natural History of Arrhythmogenic Right Ventricular Cardiomyopathy in the Boxer Dog: A Prospective Study

Abstract: BackgroundBoxer arrhythmogenic right ventricular cardiomyopathy (ARVC) is a disease that may result in sudden death or heart failure.Hypothesis/objectivesTo prospectively study the natural history of Boxer ARVC.Animals72 dogs (49 ARVC, 23 controls).MethodsBoxers >1 year of age were recruited for annual reevaluation. Controls were defined as being ≥6 years of age and having <50 ventricular premature complex (VPCs)/24 h. ARVC was defined as ≥300 VPCs/24 h in the absence of other disease. Dogs were genotyped for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 19 publications
0
28
0
Order By: Relevance
“…At the time of presentation, 4 dogs (18%) had ventricular arrhythmias, but 15 dogs (68%) were identified to have ventricular arrhythmias during the course of hospitalization. Categories of ventricular arrhythmias during hospitalization included single VPCs (Grade 1; n = 9; 41%) and R‐on‐T phenomenon or ventricular tachycardia (Grade 4; n = 6; 27%). Seven dogs (32%) had no arrhythmias during hospitalization (Grade 0).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…At the time of presentation, 4 dogs (18%) had ventricular arrhythmias, but 15 dogs (68%) were identified to have ventricular arrhythmias during the course of hospitalization. Categories of ventricular arrhythmias during hospitalization included single VPCs (Grade 1; n = 9; 41%) and R‐on‐T phenomenon or ventricular tachycardia (Grade 4; n = 6; 27%). Seven dogs (32%) had no arrhythmias during hospitalization (Grade 0).…”
Section: Resultsmentioning
confidence: 99%
“…Box plots of the highest recorded concentrations of cardiac troponin I (cTnI; a), N‐terminal pro‐B‐type natriuretic peptide (NT‐proBNP; b), and lactate (c) in 22 dogs with gastric dilatation volvulus with different categories of ventricular arrhythmias. Ventricular arrhythmias were categorized using a previously published system: 0 = no ventricular premature complexes (VPCs); 1 = single VPCs; 2 = bigeminy or trigeminy; 3 = couplets or triplets; and 4 = R‐on‐T phenomenon or ventricular tachycardia. No dogs were identified with Grade 2 or 3 ventricular arrhythmias.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we found the highest prevalence in non‐sporting (29%), toy (24%), and herding (21%) breed groups, and in multiple breeds with a predisposition for acquired heart diseases that result in a similar phenotype as Chagas cardiomyopathy. For example, German Shepherds (30% positive in this population) that can develop breed‐related inherited ventricular arrhythmias and sudden death at a very young age; Doberman Pinschers (25% positive) predisposed to idiopathic dilated cardiomyopathy characterized by cardiac enlargement, ventricular myocardial dysfunction, ventricular arrhythmias, CHF, and sudden death; and Bulldogs (54% positive) and Boxers (7% positive) that can develop arrhythmogenic right ventricular cardiomyopathy . This is an important point to consider when making a diagnosis of a heart disease that can mimic Chagas disease in a region known to have Chagas disease, as discrimination between Chagas disease and other etiologies of arrhythmias and ventricular systolic dysfunction could be difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Another important limitation was our unavailability to perform a striatin genetic mutation test in the studied Boxer dogs; the application of this test might have more precisely elucidated which animals were truly affected by Boxer ARVC. The use of an arbitrary cutoff value of VPCs on a single Holter examination for the classification of dogs as having ARVC may have led to misclassification of some patients, although the values used in this study were based on previous studies (Stern et al, 2010, Meurs et al, 2014.…”
Section: Discussionmentioning
confidence: 99%